KECENDERUNGAN POLA ASUH ORANG TUA, TIPE KEPRIBADIAN, DAN KECERDASAN EMOSIONAL MAHASISWA STKIP PGRI PACITAN - Siska Iriani; Sunardi Sunardi (Jurnal Humaniora, 2017)
This research is a quantitative research that is aimed to describe the parenting styles which applied by parents, the students personality types, and the students emotional quotient of STKIP PGRI Pacitan. The sample was taken by accidental random sampling methods. The number of respondent are 152 students from various department at STKIP PGRI Pacitan. The data is analyzed descriptively. The research finding are: (1) generally the democratic parenting styles of parents is the dominant one that is 52,63%. The permisif styles has a 30,92% and the otoriter style are 16,45%. This general inclination is also happen on each department. (2) generally the personality types on each category is equivalent. The rational type is 29,61%, the idealis type is 27,63%, the guardian type is 21,71%, and the artisan type is 21,05%. Yet if it’s seen on each department, the personality type of student is vary. (3) generally the emotional quotient of respondent is equivalent. The high emotional quotient is 32,24%, the medium emotional quotient is 34,21%, and the low emotional quotient is 33,55%.